Comparison of deep bite and open bite cases: normative data for condylar positions, paths and radiographic appearances - (:unkn) unknown (WILEY, 2004)
To compare normal overbite, deep bite and open bite cases with clinically healthy temporomandibular joints (TMJ) regarding the difference between condylar positions in centric relation (CR) and habitual or centric occlusion (CO), condylar paths and radiographic findings of condylar appearance in order to establish normative data. Three study groups of normal overbite, deep bite and open bite cases consisted each of 30 subjects with no detectable clinical signs of temporomandibular disorder. The CR-CO differences and axiographic tracings were recorded using the School Artikulator of Mack (SAM(R)) diagnostic system. Condylar shape was evaluated on panoramic radiographs. The CR-CO differences were greater in the vertical plane in open bite cases, and direction of movements from CR to CO showed great variability. Open bite cases had significantly shorter condylar paths. Radiographic findings exhibited that 23% of the total sample showed evidence of erosion and 83% evidence of flattening of condyles. The erosion rates were higher in the open bite group, but flattening was seen more often in the deep bite group. Results of this study showed that open bite cases show larger vertical CR-CO slides and, shorter protrusion paths than normal and deep overbite cases. The radiographic appearance of condyles in non-patients may also differ significantly according to vertical incisor guidance type. Deep bite cases demonstrated a higher incidence of condylar flattening. This study indicates that the clinician should be paying special attention to the TMJ status of open bite patients.
Keywords: deep bite; open bite; centric relation-centric occlusion slide; axiography; condylar flattening; condylar erosions; TEMPOROMANDIBULAR-JOINT; ORTHODONTIC TREATMENT; CENTRIC RELATION; DYSFUNCTION; OCCLUSION; MALOCCLUSION; DISORDERS; SYMPTOMS; MOVEMENT; CHILDREN